2014
DOI: 10.14740/jmc1887w
|View full text |Cite
|
Sign up to set email alerts
|

Challenging Diagnosis of a Rare Case of Spontaneous Keloid Scar

Abstract: Keloid scars are benign dermal collagenous lesions that arise in the reticular layer of the dermis as a result of a period of prolonged wound healing due to injurious cutaneous insult. It is diagnosed clinically by a history of injury preceding its appearance and its pathognomonic encroachment beyond the boundary of the original wound. There are multiple factors that predispose an individual to keloid scar formation but no single hypothesis sufficiently explained its complex pathogenesis. The spontaneity of ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…These are Dubowitz syndrome, Rubenstein-Taybi syndrome, Noonan syndrome, Goeminne syndrome and conjunctivo-corneal dystrophy [ 3 , 4 , 5 , 6 , 7 ]. Apart from these occurrences, single spontaneous keloid scar on the face has also been reported in two otherwise healthy men, in a 13-year-old on the preauricular region of the face and in an 81-year-old over the postauricular region [ 8 , 9 ]. Because of the rarity of spontaneous keloid scar, it is important to bear in mind the differential diagnosis of lesions resembling keloid scar, such as sarcoidosis and various malignant and benign tumors [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…These are Dubowitz syndrome, Rubenstein-Taybi syndrome, Noonan syndrome, Goeminne syndrome and conjunctivo-corneal dystrophy [ 3 , 4 , 5 , 6 , 7 ]. Apart from these occurrences, single spontaneous keloid scar on the face has also been reported in two otherwise healthy men, in a 13-year-old on the preauricular region of the face and in an 81-year-old over the postauricular region [ 8 , 9 ]. Because of the rarity of spontaneous keloid scar, it is important to bear in mind the differential diagnosis of lesions resembling keloid scar, such as sarcoidosis and various malignant and benign tumors [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…7 Review of litertures have shown apart from these occurrences, single spontaneous keloid scar on the face has also been reported in two otherwise healthy men, in a 13-year-old on the preauricular region of the face and in an 81-year-old over the postauricular region. 8,9 Due to rarity of conditions resulting in spontaneous keloidal scar one needs to differentiate this entity from its closer mimics such as sarcoidosis and other benign and malignant tumours. 10 The findings of our patient, did not fit with any of the syndromes metioned above nor did it represent any syndrome in particular.…”
Section: Dear Sirmentioning
confidence: 99%
“…The ratio of keloids between dark-and light-skinned people is between 5 and 18.7. Meanwhile, no case has been reported in albinos [3], [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by a wide, slightly soft, and shiny surface lump and disrupting the appearance. The exact mechanism for its occurrence has not been fully resolved, although several theories have explained its causes [1], [2], [3].…”
Section: Introductionmentioning
confidence: 99%